JURIDICAL REVIEW OF THE PROVISIONS OF THE TIME LIMIT FOR INVESTIGATION OF GENERAL CRIMES AGAINST THE PROTECTION OF THE RIGHTS OF SUSPECTS - Sahlan, Alan; Dimyati, Agus; Suwondo, Sutiyono (Fakultas Hukum Universitas Swadaya Gunung Jati, 2024)
The phenomenon of criminal law enforcement today is increasingly losing direction and is even considered to have reached its lowest point, the justice-seeking community complains about the criminal investigation process (general) which is convoluted, protracted and there is even no end to the solution, this situation clearly does not provide legal certainty, justice and benefits in law enforcement, moreover there will be violations of the rights of suspects, one of the causes of this situation is the absence of The provisions of the investigation time limit (norm vacuum), which gives the investigator the opportunity to abuse his authority. Therefore, the purpose of this study is to find out the provisions of the time limit for the investigation of general crimes related to the protection of the human rights of suspects in the Criminal Procedure Code (KUHAP) and to analyze the setting of the time limit for the investigation of general crimes in the criminal procedure law that will be dated. The research method used in this study is using the type of normative legal research with the approach used in this study being the statute approach and the conceptual approach, with the research specification being descriptive analytical, while the legal material collection technique used in this study is by using document studies. namely documents obtained from the Jatanrasa Unit of the Sumber Police. Based on the results of the study, it shows that there is no provision that regulates the time limit for the investigation of the suspect from the beginning of the investigation to the transfer of the trial case, so that the status of the suspect depends on the investigation process. The absence of a time limit in the investigation of suspects causes legal uncertainty guaranteed by Articles 28D and 281 paragraph (2) of the 1945 Constitution, therefore in the Draft Criminal Code there is a regulation of the time limit for investigation as stipulated in article 48 of the RUUKUHAP. Paragraph (1) and Paragraph (3)